2023
DOI: 10.3892/mmr.2023.13126
|View full text |Cite
|
Sign up to set email alerts
|

miR‑3120/Hsc70 participates in forced swim stress‑induced mechanical hyperalgesia in rats in an inflammatory state

Shiqin Xu,
Shijiang Liu,
Juan Yang
et al.

Abstract: The heat shock cognate 71 kda protein (Hsc70) is a stress-inducible aTPase that can protect cells against harmful stimuli. Transient receptor potential vanilloid 1 (TrPV1) is a well-documented nociceptor. notably, Hsc70 can inhibit TrPV1 expression and function, suggesting that Hsc70 may have pain regulation potential. However, the role of Hsc70 in stress-induced hyperalgesia remains unclear. in the present study, the participation of Hsc70 and its regulator microrna (mir)-3120 were investigated in forced swim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The exacerbation of inflammatory hyperalgesia through chronic and repeated sound stress involves contributions from both the sympathoadrenal (epinephrine) and the hypothalamic-pituitary adrenal (corticosterone) neuroendocrine stress axes ( 46 , 47 ). The contribution of nociceptors in stress-induced exacerbation of inflammatory hyperalgesia is supported by a recent study ( 48 ), which demonstrated that cellular pathways involving miR-3120 regulation on Hsc70, leading to the overexpression of TRPV1 in DRG neurons, mediate FSS-induced mechanical hyperalgesia under inflammatory conditions. FSS also enhances inflammatory responses arising from the masseter muscle ( 14 , 49 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The exacerbation of inflammatory hyperalgesia through chronic and repeated sound stress involves contributions from both the sympathoadrenal (epinephrine) and the hypothalamic-pituitary adrenal (corticosterone) neuroendocrine stress axes ( 46 , 47 ). The contribution of nociceptors in stress-induced exacerbation of inflammatory hyperalgesia is supported by a recent study ( 48 ), which demonstrated that cellular pathways involving miR-3120 regulation on Hsc70, leading to the overexpression of TRPV1 in DRG neurons, mediate FSS-induced mechanical hyperalgesia under inflammatory conditions. FSS also enhances inflammatory responses arising from the masseter muscle ( 14 , 49 ).…”
Section: Discussionmentioning
confidence: 78%
“…In addition to inducing non-inflammatory hyperalgesia in naïve animals, psychophysical stress amplifies hyperalgesic responses in animals experiencing inflammatory conditions ( 44 48 ). The exacerbation of inflammatory hyperalgesia through chronic and repeated sound stress involves contributions from both the sympathoadrenal (epinephrine) and the hypothalamic-pituitary adrenal (corticosterone) neuroendocrine stress axes ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%